2019
DOI: 10.3390/en12142646
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations on Heat Transfer of Bare Tubes in a Bubbling Fluidized Bed with Respect to Better Heat Integration in Temperature Swing Adsorption Systems

Abstract: In this paper experimental and numerical investigations on heat transfer within a bubbling fluidized bed will be presented with respect to better heat integration in continuous temperature swing adsorption (TSA) processes for biogas upgrading. In the literature, mainly heat transfer measurements with glass or sand particles are carried out, thus special reference measurements with adsorbent material in a fluidized bed are missing. Therefore firstly, a series of experiments were carried out in the fluidized bed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 44 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The most recent experimental research on horizontally submerged tubes and fluidized beds examined the effect of axial tube position 7 , heater inclinations 8 , tube diameter, moisture 9 , and velocity 10 on small particles. Vogtenhuber et al 11 found identical values of heat transfer coefficients for single tubes as well as inline and staggered arrangements in amine bulk material. Nonetheless, Lechner et al 12 studied heat flow dependency of horizontal tube diameter in large particle fluidized beds.…”
Section: Introductionmentioning
confidence: 91%
“…The most recent experimental research on horizontally submerged tubes and fluidized beds examined the effect of axial tube position 7 , heater inclinations 8 , tube diameter, moisture 9 , and velocity 10 on small particles. Vogtenhuber et al 11 found identical values of heat transfer coefficients for single tubes as well as inline and staggered arrangements in amine bulk material. Nonetheless, Lechner et al 12 studied heat flow dependency of horizontal tube diameter in large particle fluidized beds.…”
Section: Introductionmentioning
confidence: 91%
“…For the heat exchange of high-temperature granular matter, moving bed heat exchangers (MBHE) with low cost, clean energy and wide granularity adaptability are gradually applied to industrial waste heat recovery [6] and concentrating solar power [7]. However, compared with the fluidized bed [8], the heat transfer performance of the MBHE needs to be further improved [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moving bed heat exchanger (MBHE), with the advantages of low cost, clean energy and wide particle size adaptation, is gradually applied in many high temperature waste heat recovery industries [1], such as slag [2], cement [3], coke [4] and concentrated solar power (CSP) [5]. For the MBHE, the granular flow inside is driven by the gravity, and the heat transfer is relatively lower [6] as compared with packed bed [7] or fluidized bed [8]. Therefore, it is important to improve the heat transfer of particle flow in the MBHE.…”
Section: Introductionmentioning
confidence: 99%